Christianity and Infant Health in India - Nidhiya Menon; Kathleen McQueeney (Institute for the Study of Labor (IZA), 2015)
This paper studies child health in India focusing on differences in anthropometric outcomes between the three main religions Hindus, Muslims and Christians. The results indicate that Christian infants have higher height-for-age z-scores as compared to infants of other religious identities, and that this is especially true for infant girls in states with a relatively large Christian presence. We instrument for Christian identity today using data on the location of Protestant and Christian missions, the incidence of epidemic diseases and natural disasters, and political crises (wars) that mission establishing countries were engaged in during India's colonial history. The results are robust to a series of checks for instrument validity and omitted variables, and indicate that by inculcating awareness and spreading knowledge on sanitation and the scientific underpinnings of disease, the advent of Christianity has long-term health implications for India's children today.
Keywords: O12; I15; Z12; 330; child health; religion; Christian; Hindu; Muslim; India